CARICOM CET: an OECS solution and its implications - Mitchell, C.L. (OECS Economic Affairs Secretariat St. John'sAC, 1992)
Takes an objective view of the CARICOM CET, its implications for the OECS and the CARICOM Region and indicates where we should go from here. Examines aspects such as its genesis and structure; implications of the CET for the MDCs and LDCs of CARICOM; proposed OECS recommendations for amending the CARICOM CET; and an OECS state for a CET.